Case report: Waldenstrom macroglobulinemia with systemic amyloidosis as the main manifestation - Yin, Junjing; Zhou, Xia; Yu, Shuyuan; Wu, Hongying; Zhong, Yuping (Frontiers in Medicine, 2024)
Systemic amyloidosis is a rare protein misfolding and deposition disorder leading to progressive organ failure. Waldenström macroglobulinemia (WM) with systemic amyloidosis as the main manifestation is even rarer. The patient in this study presented with recurrent diarrhea and had not been diagnosed in other hospitals on multiple occasions. Later, his diarrhea worsened and was accompanied by sunken edema of both lower limbs and dizziness. Renal biopsy showed deposits of PAS light-staining material in the glomeruli, interstitium, and small arteries, which stained positively with Congo red. Cardiac ultrasound showed interventricular septum thickening of 17 mm, right ventricular wall myocardial thickening of approximately 0.6 cm, and septal thickening of approximately 0.5 cm, considering myocardial amyloidosis. Electromyography showed abnormal peripheral nerve conduction. Lymphoplasmacytic cells were found in the bone marrow. Taken together, he was diagnosed with WM. He was treated with a BR (Bendamustine + Rituximab) regimen. After 6 courses, the patient’s discomfort was relieved, his weight gained 5 kg, the level of serum IgM and dFLC decreased, and cardiac and renal assessments were more relieved. The patient has been followed up for more than 1 month.